windfall '91 : 25 artists representing 8 European Countries : Seamen's Mission : Glasgow. (Glasgow : City of Glasgow District Council, 1991)
Achour, Boris ; Bertenburg, Achim ; Byrne, Gerard ; Dãrdaña, Josep ; Drachman, Anita ; Heise, Jens ; Janssen, Edwin ; Lapuks, Michael ; McMullan, Emma ; Regler, Norman ; Reynaud, Sylvie ; Ryan, Bláithnaid ; Staal, Niels ; Allen, David ; Barclay, Claire ; Boyce, Martin ; Buchanan, Roderick ; Coley, Nathan ; Gordon, Douglas ; etc.
winfall '91 : 25 artists representing 8 European Countries : Seamen's Mission : Glasgow was an artists initiated project organised by the participants in glasgow 1991
boek